2011
DOI: 10.1038/mp.2011.136
|View full text |Cite
|
Sign up to set email alerts
|

African ancestry protects against Alzheimer's disease-related neuropathology

Abstract: Previous studies in dementia epidemiology have reported higher Alzheimer's disease rates in African-Americans when compared with White Americans. To determine whether genetically determined African ancestry is associated with neuropathological changes commonly associated with dementia, we analyzed a population-based brain bank in the highly admixed city of São Paulo, Brazil. African ancestry was estimated through the use of previously described ancestry-informative markers. Risk of presence of neuritic plaques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 38 publications
5
51
0
4
Order By: Relevance
“…While the primary result was that African ancestry is protective of AD pathology, there was also a tendency of higher odds of Lewy body pathology in persons of African ancestry; however, it did not reach significance and was not a major focus of the article. 23 The high frequency of Lewy body pathology among black decedents in our sample may reflect a selection bias for clinic samples. Lewy body disease, with and without coexisting AD pathology, is associated more with behavioral abnormalities, such as hallucinations and REM sleep behavior disorder, than clinical AD.…”
Section: Resultsmentioning
confidence: 99%
“…While the primary result was that African ancestry is protective of AD pathology, there was also a tendency of higher odds of Lewy body pathology in persons of African ancestry; however, it did not reach significance and was not a major focus of the article. 23 The high frequency of Lewy body pathology among black decedents in our sample may reflect a selection bias for clinic samples. Lewy body disease, with and without coexisting AD pathology, is associated more with behavioral abnormalities, such as hallucinations and REM sleep behavior disorder, than clinical AD.…”
Section: Resultsmentioning
confidence: 99%
“…These studies focused mainly on highly educated Caucasian subjects with an average age of death of over 70 years. The study participants investigated in the present study were relatively younger, had a greater range of exposure to education, (22) and came from an ethnically diverse city (58). The slightly lower prevalence of TDP-43 proteinopathy observed in our series may reflect the lower age of the study subjects, because TDP-43 pathology is more prevalent in older individuals (6, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Rosenberg et al [30] found that persons with a greater degree of Cherokee Indian heritage had a lower risk of developing AD. Until now, one single report sought to investigate the relationship between genomic ancestry and the AD phenotype in Brazil [31]. According to their report, African ancestry protects against AD-related neuropathology.…”
Section: Discussionmentioning
confidence: 99%